2021
DOI: 10.1101/2021.04.13.21255442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender differences in the determinants of willingness to get the COVID-19 vaccine among the working-age population in Japan

Abstract: Many factors are related to vaccination intentions. However, gender differences in the determinants of intention to get the coronavirus disease 2019 (COVID-19) vaccine have not been fully investigated. This study examined gender differences in the determinants of willingness to get the COVID-19 vaccine among the working-age population in Japan. We conducted a cross-sectional study of Japanese citizens aged 20-65 years using an online self-administered questionnaire in December 2020. Logistic regression analysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
2
7
2
Order By: Relevance
“…These findings are similar to those from other studies [13,19,21,22,[28][29][30]. The higher vaccine non-acceptance in females and younger age is consistently reported in other studies and attributed to their low-risk perception of COVID-19 and additionally the higher vaccine safety concern especially in females [13,19,21,28,29,31,32]. The low-risk perception in some of HCWs in our study may be related to the relatively high recovery and low mortality rates observed in most Ethiopian hospitals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are similar to those from other studies [13,19,21,22,[28][29][30]. The higher vaccine non-acceptance in females and younger age is consistently reported in other studies and attributed to their low-risk perception of COVID-19 and additionally the higher vaccine safety concern especially in females [13,19,21,28,29,31,32]. The low-risk perception in some of HCWs in our study may be related to the relatively high recovery and low mortality rates observed in most Ethiopian hospitals.…”
Section: Discussionsupporting
confidence: 93%
“…We identified several groups with higher vaccine non‐acceptance: HCWs who were female, younger, non‐physicians, unconcerned about COVID‐19 and the risk of getting infected at work. These findings are similar to those from other studies [ 13 , 19 , 21 , 22 , 28 , 29 , 30 ]. The higher vaccine non‐acceptance in females and younger age is consistently reported in other studies and attributed to their low‐risk perception of COVID‐19 and additionally the higher vaccine safety concern especially in females [ 13 , 19 , 21 , 28 , 29 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…As of October 4, 2021, the proportion of the population who had received the first and second doses was 67.2% and 58.2%, respectively [29]. Many studies have been conducted to explore the determinate of vaccine intention among Japanese: women, young people, single people, urbanites, people with low socioeconomic status, and those with severe psychological distress were more likely to be hesitant to accept the COVID-19 vaccine [30][31][32][33][34]. However, little is known about the attitudes toward COVID-19 vaccination among migrants in Japan, despite a growing foreign population.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the majority of the population had some level of initial vaccine hesitancy to receive a COVID-19 vaccine [9,10]. Nevertheless, by the end of December 2021, approximately 80% of the population had received two vaccine doses [11].…”
Section: Introductionmentioning
confidence: 99%